2014
DOI: 10.5644/ama2006-124.111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diabetes mellitus and hypertension on work productivity

Abstract: Diabetes mellitus appears to reduce an individual's ability to work in comparison to patients with hypertension. There is a need to set up a diabetes mellitus prevention program and to develop and implement effective targeted intervention to help workers to manage their disease better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
10
0
5
Order By: Relevance
“…The present study also showed higher levels of absenteeism, presenteeism, overall work impairment and activity impairment, after adjusting for covariates, in physically impaired older T2DM patients. These findings are in line with another study that found loss of work productivity in a quarter of patients with T2DM (mean age ¼ 55.08) and 1.5 times use of sick leave in patients with T2DM compared with patients with hypertension 39 . Other studies have shown loss of work productivity is greater in patients with T2DM who experience diabetic neuropathy compared to patients with T2DM who do not experience diabetic neuropathy 40 and that non-severe hypoglycemia is associated with lost work productivity 41 .…”
Section: Discussionsupporting
confidence: 92%
“…The present study also showed higher levels of absenteeism, presenteeism, overall work impairment and activity impairment, after adjusting for covariates, in physically impaired older T2DM patients. These findings are in line with another study that found loss of work productivity in a quarter of patients with T2DM (mean age ¼ 55.08) and 1.5 times use of sick leave in patients with T2DM compared with patients with hypertension 39 . Other studies have shown loss of work productivity is greater in patients with T2DM who experience diabetic neuropathy compared to patients with T2DM who do not experience diabetic neuropathy 40 and that non-severe hypoglycemia is associated with lost work productivity 41 .…”
Section: Discussionsupporting
confidence: 92%
“…According to the World Health Organization (WHO, 2018), NCDs are currently responsible for more than 70% deaths worldwide. Furthermore, NCDs affect quality of life (Simcoe et al, 2019) and productivity (Magliano et al, 2018), leading to an economic burden on families, communities and countries (Krstović-Spremo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The estimated cost of diagnosed diabetes in 2012 was US$245 billion, including US$176 billion in direct medical costs and US$69 billion in reduced productivity (American Diabetes Association [ADA], 2013). Although many adults with diabetes are productive members of the workforce, loss of work productivity has been associated with the presence of diabetes (Krstovic-Spremo et al, 2014). Diabetes self-management (DSM) is a lifelong process and includes healthy nutritional habits, being physically active, taking medication, and monitoring blood glucose, with the goal of preventing both acute and chronic complications (Haas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%